Cloud vs edge: Who serves the Internet‐of‐Things better?. Issue 5 (26th July 2018) - Maamar, Zakaria; Baker, Thar; Sellami, Mohamed; Asim, Muhammad; Ugljanin, Emir; Faci, Noura
Abstract : Usually announced to the ICT community as rivals in the Internet‐of‐Things (IoT) context, cloud and edge could work together according to their respective capabilities. Today's IoT applications can be dependent neither on a single technology (either SQL or noSQL) nor on a single operation model (either centralized or decentralized). The multiple challenges are complexity of user scenarios, multiplicity of things, sensitivity of data, etc. This paper raises the question of who serves IoT better? Cloud, only; edge, only; or both together. To answer this question, clouds' and edges' duties are identified and then a set of collaborative scenarios are discussed with respect to these duties.